Development of a research platform for dissecting phenotype-genotype associations in rice (Oryza spp.) - Tung, Chih-Wei; Zhao, Keyan; Wright, Mark H.; Ali, M. Liakat; Jung, Janelle; Kimball, Jennifer; Tyagi, Wricha; Thomson, Michael J.; McNally, Kenneth; Leung, Hei; Kim, Hyunjung; Ahn, Sang-Nag; et al. (Springer, 2010)
We present an overview of a research platform that provides essential germplasm, genotypic and phenotypic data and analytical tools for dissecting phenotype–genotype associations in rice. These resources include a diversity panel of 400 Oryza sativa and 100 Oryza rufipogon accessions that have been purified by single seed descent, a custom-designed Affymetrix array consisting of 44,100 SNPs, an Illumina GoldenGate assay consisting of 1,536 SNPs, and a suite of low-resolution 384-SNP assays for the Illumina BeadXpress Reader that are designed for applications in breeding, genetics and germplasm management. Our long-term goal is to empower basic research discoveries in rice by linking sequence diversity with physiological, morphological, and agronomic variation. This research platform will also help increase breeding efficiency by providing a database of diversity information that will enable researchers to identify useful DNA polymorphisms in genes and germplasm of interest and convert that information into cost-effective tools for applied plant improvement.